ChemInform Abstract: Van der Waals Dispersion Interactions in Molecular Materials: Beyond Pairwise Additivity. Issue 29 (July 2015) - Reilly, Anthony M.; Tkatchenko, Alexandre
Abstract Review: [115 refs.